2006
DOI: 10.1080/00343400500449259
|View full text |Cite
|
Sign up to set email alerts
|

Population growth in European cities: Weather matters – but only nationally

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 20 publications
13
126
2
5
Order By: Relevance
“…As such, any migration model which attempts to account for Italian interregional mobility patterns in general will be mis-specified because the underlying processes of these two simultaneously-operating migration systems are very different. Moreover, our results also differ markedly from those of Cheshire & Magrini (2006) in that our observations suggest that natural amenity-driven migration in Italy only operates within the same region, not at the level of the country as a whole. As far as we are aware, this is the first time that the different types of simultaneously-operating short distance and long distance interregional migration flows have been decomposed and analysed for a country in this particular way, and it will be instructive to identify whether the patterns uncovered in Italy are also reflected in other countries.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…As such, any migration model which attempts to account for Italian interregional mobility patterns in general will be mis-specified because the underlying processes of these two simultaneously-operating migration systems are very different. Moreover, our results also differ markedly from those of Cheshire & Magrini (2006) in that our observations suggest that natural amenity-driven migration in Italy only operates within the same region, not at the level of the country as a whole. As far as we are aware, this is the first time that the different types of simultaneously-operating short distance and long distance interregional migration flows have been decomposed and analysed for a country in this particular way, and it will be instructive to identify whether the patterns uncovered in Italy are also reflected in other countries.…”
Section: Discussioncontrasting
confidence: 57%
“…The vast majority of evidence from Europe suggests that interregional migration is primarily driven by a disequilibrium mechanism in which, allowing for life-cycle effects (Fielding, 1993), migration is mainly a response, albeit slow, to spatial differences in economic factors such as wages and employment opportunities (Faggian & McCann, 2009a). Natural amenities, such as climate, do not affect migration to the extent found in the US (Cheshire & Magrini, 2006). Ferguson et al (2007) reach similar conclusions for Canada.…”
Section: Introductionsupporting
confidence: 58%
“…For whatever reason, in an earlier paper (Cheshire and Magrini, 2006) we showed that while population movement across the EU of 12 between 1980 and 2000 did significantly respond to generalised differences in economic advantage (as reflected, for example, in the systematic spatial effects of European integration or regional inheritances of old resource-based industries), and also responded to climatic differences, the evidence was inconsistent with full spatial equilibrium. The response of population movement to economic factors was sluggish; net migration rates between comparably sized regions in the USA are fifteen times greater than in Europe (Cheshire and Magrini, 2006). Perhaps more telling, population movement responded strongly to climatic differences but only to climatic differences within countries.…”
mentioning
confidence: 84%
“…Both processes are worth investigating but understanding one illuminates the other. The finding reported in Cheshire and Magrini (2006) that full spatial equilibrium is not a reasonable assumption in the context of European spatial development therefore focuses additional interest in understanding better what factors drive urban economic growth differentials -the subject of this paper.…”
Section: Issues and Approachmentioning
confidence: 99%
“…Findings with respect to amenities are clear. Area measures of population and migration as well as household location decisions are significantly related to climate (Mueser and Graves 1995, Clark and Murphy 1996, Hunt and Mueller 2004, Cheshire and Magrini 2006, Rappaport 2007, Poston et al 2009, Eichman et al 2010), air quality (Seig et al 2004, Bayer et al 2008, recreational opportunities (Duffy-Deno 1998, Lewis et al 2002), cultural amenities (Clark and Hunter 1992), and crime rates (Gottlieb and Joseph 2006). Housing prices and wages are endogenous to area-level migration (Mueser and Graves 1995), and so these variables are typically excluded from analyses with aggregate data.…”
Section: Introductionmentioning
confidence: 99%